Good Corporate Governance, Intellectual Capital, And Operational Efficiency: Affect Company Value - Leny Suzan; Dekri Ardiansyah (Jurnal Akademi Akuntansi, 2023)
Purpose: As the best measure of company health, companies that have gone public often try to increase shareholder value. One of them is the company value because it describes the condition of the company. This study attempts to find out how corporate governance, intellectual capital, and operational efficiency affect company value. Methodology/approach: This study uses quantitative data from 15 companies in the IDX BUMN20 Stock Index for 2018–2021. Findings: The research findings show that institutional ownership and intellectual capital significantly and beneficially affect company value. Meanwhile, independent commissioners, audit committees, managerial ownership, and operational efficiency have no visible impact. This shows how institutional ownership is a component that can improve performance through supervision. At the same time, intellectual capital management is proven to maximize the company's value. Practical and Theoretical contribution/Originality: The implication is that companies that disclose intellectual capital and uphold institutional ownership will give a positive signal to investors in making investment decisions. Research Limitation: Future studies may be useful to compare firm values during and after the COVID-19 pandemic by using the factors examined in this research to provide a specific picture of how investors respond to the two conditions and their relation to signal theory.